Engineering trustworthy systems : get cybersecurity design right the first time - Saydjari, O. Sami (McGraw-Hill Education, 2018)
This professional guide shows, step by step, how to design and deploy highly secure systems on time and within budget. The book offers comprehensive examples, objectives, and best practices and shows how to build and maintain powerful, cost-effective cybersecurity systems. Readers will learn to think strategically, identify the highest priority risks, and apply advanced countermeasures that address the entire attack space. Engineering Trustworthy Systems: Get Cybersecurity Design Right the First Time showcases 35 years of practical engineering experience from an expert whose persuasive vision has advanced national cybersecurity policy and practices--